Cuckoo search assisted fuzzy logic algorithm for smart WSN routing system. (14th June 2022) - Sundaram, Kuppusamy Mohana; Nageswari, D.; Prakash, J.
This paper aims to provide the secured communication between the networks of WSN and this security is provided by creating the secrete keys between the neighbouring keys. In this paper, the location-based key (LBK) management is utilised. This paper also addresses the performance of the network more efficiently by cuckoo search assisted fuzzy logic algorithm. In this paper, each node is analysed to find the occurred threats and to find the security levels. This paper uses the cuckoo search assisted fuzzy logic algorithm to improve the network performance and the security level is enhanced by location-based key (LBK) management. By this method, the load at each node is balanced with the improved security level and also the lifespan of the network is improved. This proposed method demonstrates the level of security in communication between the nodes. By using this algorithm the delay, performance, error and the security level of the network are identified. The cuckoo search assisted fuzzy logic algorithm is the novel method, which is used to get better performance of the network and to improve the communication security.